2004
DOI: 10.1007/s10227-004-0803-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action and Emerging Role of Immune Response Modifier Therapy in Dermatologic Conditions

Abstract: Immune response modifiers (IRMs) are agents that target the body's immune system (i.e., cytokines, receptors, and inflammatory cells) to combat disease. Topical IRM therapies, which encompass both proinflammatory and immunosuppressive therapeutics, have been used to successfully treat a number of dermatologic conditions. Proinflammatory treatments include Toll-like receptor agonists (e.g., imiquimod 5% cream) and interferon (e.g., interferon-alpha) therapies, which have been used in the treatment of external g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 108 publications
(114 reference statements)
0
14
0
1
Order By: Relevance
“…Imiquimod [1‐(2‐methylpropyl)‐1, H‐imidazo(4,5‐c), quinolin‐4‐amine] is an immune response modifier which activates immune cells via toll‐receptor (TLC) 7, initiating a cascade that leads to the induction of cytokines such as IFN‐alfa, gamma and IL‐12, which promote a Th‐1 immune response. These cytokines are capable of inducing psoriasis 8,9 . Evidence that psoriasis is an immune‐mediated disorder comes from laboratory studies, clinical observation, and use of targeted therapies 10 .…”
mentioning
confidence: 99%
“…Imiquimod [1‐(2‐methylpropyl)‐1, H‐imidazo(4,5‐c), quinolin‐4‐amine] is an immune response modifier which activates immune cells via toll‐receptor (TLC) 7, initiating a cascade that leads to the induction of cytokines such as IFN‐alfa, gamma and IL‐12, which promote a Th‐1 immune response. These cytokines are capable of inducing psoriasis 8,9 . Evidence that psoriasis is an immune‐mediated disorder comes from laboratory studies, clinical observation, and use of targeted therapies 10 .…”
mentioning
confidence: 99%
“…In another study, 5% imiquimod was applied to the eyelids with good results in terms of clearance, but the authors state that the excellent recurrence rate was tentative because of the short-term follow-up time [5]. Imiquimod is one of a new class of immune response modifiers being used for various dermatological conditions [6]. The mechanism of action of imiquimod cream in treating BCC lesions is unknown, although it has been suggested that it may increase the infiltration of lymphocytes, dendritic cells and macrophages into the tumour lesion [7].…”
Section: Discussionmentioning
confidence: 96%
“…The immune response modifier, imiquimod (IMQ), acts through two members of the toll-like receptor (TLR) family, TLR7 and/or 8, which recognize microbial pathogens or their metabolic products, and function as primary sensors of the innate immune system (Ambach, A, et al , 2004, Sauder, DN, 2004, Lai, Y, et al , 2008). These TLR are cell surface receptors that, when activated, stimulate production of epidermis-derived, interferon-alpha, tumour necrosis factor, and interleukin-1α (Sauder, DN, 1990, Barland, CO, et al , 2004, McInturff, JE, et al , 2005, Takeuchi, O, et al , 2009).…”
Section: Discussionmentioning
confidence: 99%